Ma Rainey's phonograph. Issue 3 (2nd September 2018) - DeCristo, Jeramy
Abstract : This essay engages a series of performance routines by the blues artist Gertrude "Ma" Rainey, as a way of critiquing the epistemological tenets of sound reproduction technology. Between 1923 and 1925 Gertrude "Ma" Rainey carried out an elaborate quasi-burlesque performance routine in which she sang while hidden inside a giant phonograph; this routine precisely references and troubles the legacy of black sounds and bodies and their conflicted forms of capture andembodiment through sonic technologies. I think about how black sounds and bodies have been rendered as documentary objects within sonic and visual performance contexts and how this history is both referenced and complicated in Ma Rainey's performances. I argue further that Rainey's performance illustrates how sonic technologies always require, what I term black documentary embodiment, through the sonic and the visual. To this end I illustrate how reducing black art to an evidentiary object was central to the phonograph's material and epistemological construction. In addition to analyzing Rainey's performance I briefly engage the contemporaneous visual culture of the blues as a means to trace the legacy of black documentary embodiment within a longer visual-sonic tradition.